(untitled) (Journal of actual problems of jurisprudence, 2024)
This article is devoted to the study of the institute of succession in relation to the field of intellectual property law. The analysis of norms and theoretical provisions on succession indicates that this aspect has not been studied enough in Kazakhstan, which leads to confusion and ambiguity of terminology, due to the imperfection of legislation regulating relations in the field of intellectual property, problems arise in law enforcement. This situation unwittingly creates significant difficulties for practice regarding the results of intellectual activity, means of individualization, the realization of exclusive rights to them and the correct understanding of the terms that make up the content of succession. The article analyzes various approaches to the concept of succession, its classification. The article provides a detailed study on such aspects of intellectual property law as the correct application of the conceptual apparatus, problems in the Law of the Republic of Kazakhstan on Copyright and Related Rights, contracts in the field of intellectual property and many others. In particular, the author substantiates the concepts of «transition», «transfer», «provision», «disposal». Special attention is paid to the problem of the correlation of the contract of assignment of exclusive rights and assignment, inconsistencies in the concepts of license and copyright agreements. The opinion is substantiated why the contract of the author’s order cannot be included in the category of contract contracts. Keywords: intellectual property right, exclusive rights, transfer, transfer, provision, alienation, disposal.